2018
DOI: 10.21851/obr.42.01.201803.62
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of online questions about dental hygienist: Case report in Naver Intelligent Network

Abstract: ·············································································································································································Current trends note that individuals utilize the information provided through online knowledge search services, to solve their curiosity for news and world events, as well as to read information written by others and acquire new knowledge on a variety of subjects. The purpose of this study was to analyze the questions about dental hygienist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…A previous study analyzed the inquiries retrieved from the Q & A section on an Internet portal site using the Korean names for dental hygienists. This study confirmed that the words used in most inquiries were related to entrance examination, employment, and the job of dental hygienists, depending on age groups 11) . Another study analyzed inquiries posted by dental hygienists and the general public through various Internet sites, and reported that words relating to the job or career choice were used by the general public, and words relating to dental practice and turnover were used by dental hygienists 12) .…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…A previous study analyzed the inquiries retrieved from the Q & A section on an Internet portal site using the Korean names for dental hygienists. This study confirmed that the words used in most inquiries were related to entrance examination, employment, and the job of dental hygienists, depending on age groups 11) . Another study analyzed inquiries posted by dental hygienists and the general public through various Internet sites, and reported that words relating to the job or career choice were used by the general public, and words relating to dental practice and turnover were used by dental hygienists 12) .…”
Section: Introductionsupporting
confidence: 75%
“…First is the consideration for main age group that may generate the collected text data. A previous study investigated inquiries retrieved from Naver "Jishik-iN" using Korean words for dental hygienists as search words, and reported that the proportion of inquiries focused on employment and entrance exams were high, indicating that the collected data were primarily originated from the younger age group 11) . In the present study, words related to admission to the Department of Dental Hygiene (chiwisaeng-gwa, 16th; chiwisaenghag-gwa, 86th), College (daehag, 24th), and University (daehaggyo, 58th) were extracted as frequently used words, and an association rule was found between the words "chiwisaeng-gwa" and "daehag".…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted on dental treatment 6) or demand for information on dental hygienists 7,8) using Naver knowledge; but it has been a while since these studies were conducted, although the rate of accumulation of data on the internet has increased exponentially every year. It is, therefore, necessary to examine whether the internet has provided the patient with correct dental treatment information.…”
Section: Introductionmentioning
confidence: 99%